Enhancing the capacitance of TiO2 nanotube arrays by a facile cathodic reduction process - Zhou, He; Zhang, Yanrong (Journal of power sources, 2013)
TiO2 nanotube arrays are modified by a facile cathodic reduction process treatment and the results are discussed in terms of their electrochemical activity and conductivity. The instrumental characterizations such as X-ray photoelectron spectroscopy and Raman spectroscopy indicate that the formation of oxygen vacancies in the lattice and introduction of hydroxyl groups on the surface of TiO2 take place. The capacitance of the modified sample is found to be 13 times larger than the pristine TiO2 nanotube arrays. This work reveals a feasible and simple method to improve electrochemical activity and conductivity of TiO2 for supercapacitors application. •TiO2 nanotube arrays were modified by a facile cathodic reduction process.•Oxygen vacancies were formed and hydroxyls were introduced on the surface of TiO2.•The electrochemical activity and conductivity of modified sample were improved.•The modified sample showed much enhanced capacitance over the pristine one.